Into the Intracellular Logistics of Cross-Presentation - Sadaka, Charlotte; Neefjes, Jacques (Frontiers in Immunology, 2012)
The induction of cytotoxic CD8+ T cell responses requires the presentation of antigenic peptides by MHC class I molecules (MHC I). MHC I usually present peptides derived from endogenous proteins. However, some subtypes of dendritic cells (DCs) have developed the ability to efficiently present peptides derived from exogenous antigens on MHC I via a process called cross-presentation. Cross-presentation is intimately linked to the induction of anti-viral, -bacterial and -tumor cytotoxic T cell (CTL) responses, as well as a wide variety of CTL-mediated diseases and transplant rejections. The molecular and cellular mechanisms underlying cross-presentation have been studied intensively since its original description, yet understanding of this process is incomplete and on the forefront of immunological research. Numerous pathways and models, some of them conflicting, have been described so far. Here, we review the various pathways reported as involved in cross-presentation, highlighting the complexity of this process. We also discuss in detail the different intracellular steps required, from antigen capture and routing, to processing and finally peptide loading, emphasizing the need for a better understanding of the cell biology of this phenomenon.